Does Capital Account Liberalization Affect the Financial Stability: Evidence from China - Yuanyuan Shen, Yuanyuan Shen; Yang, Lu (Journal of Reviews on Global Economics, 2015)
This paper seeks to investigate the relationship between capital account liberalization and the financial stability in China. Furthermore, The Finite Distributed Lag Model is employed to quantify relationship between capital account liberalization and monetary crisis. And a general conclusion can be drawn that capital account liberalization is harmful to the stability official market in one year period, while the overall capital account liberalization effect can facilitate China’s financial stability in a long run. Moreover, some suggestions are provided on China’s capital account liberalization policies.